Supercomplex Organization of the Electron Transfer System in Marine Bivalves, a Model of Extreme Longevity. Issue 2 (6th December 2021) - Rodríguez, Enrique; Radke, Amanda; Hagen, Tory M; Blier, Pierre U
Abstract: The mitochondrial oxidative stress theory of aging suggests that the organelle's decay contributes to the aging phenotype via exacerbated oxidative stress, loss of organ coordination and energetics, cellular integrity, and activity of the mitochondrial electron transfer system (ETS). Recent advances in understanding the structure of the ETS show that the enzymatic complexes responsible for oxidative phosphorylation are arranged in supramolecular structures called supercomplexes that lose organization during aging. Their exact role and universality among organisms are still under debate. Here, we take advantage of marine bivalves as an aging model to compare the structure of the ETS among species ranging from 28 to 507 years in maximal life span. Our results show that regardless of life span, the bivalve ETS is arrayed as a set of supercomplexes. However, bivalve species display varying degrees of ETS supramolecular organization with the highest supercomplex structures found in Arctica islandica, the longest-lived of the bivalve species under study. We discuss this comparative model in light of differences in the nature and stoichiometry of these complexes and highlight the potential link between the complexity of these superstructures and longer life spans.